Cardiac Myxoma Single Center Experience - Dawood, Adil Kh. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: cardiac myxoma is the most frequent primary cardiac tumour comprising 30 to 50%, they are benign tumours. They are most often reported in women in the third to sixth decade of life. Objectives: is to evaluate the incidence of surgery of cardiac myxomas and their presentation and outcome in IbnAl-NafeesTeaching hospital over 10 years. Patient and Methods: This is a retrospective study that was conducted in Ibn Al-Nafees Hospital from January 2005 to December 2014 on patients with cardiac myxoma. Twenty-five patients diagnosed pre-operatively as having cardiac myxoma, they were admitted to the hospital and underwent clinical evaluation, investigation, and surgical treatment. Result: Cardiac myxomas constituted 1% of the total cardiac operations at our institute, the twenty-five patients who were studied were operated upon, the mean age of patients was 49 years and male-female ratio was 1:3.Occurrence of myxoma was more common in the left atrium 88% followed by right atrium 8% while only 1 patient had myxoma in right ventricle. One recurrence was noticed after surgery, only one early death observed in this study. Conclusion: Early surgical intervention with complete resection of the tumour is essential for the cure of the disease and to prevent tumour recurrence with subsequent reoperation that expose the patient to more serious complications, Echocardiography is the ideal diagnostic tool and it is needed in the long term follow-up of the patients.